The Janus-faced nature of debt: Results from a data-driven cointegrated SVAR approach - Mattia Guerini; Alessio Moneta; Mauro Napoletano; Andrea Roventini (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2017)
In this paper, we investigate the causal effects of public and private debts on U.S. output dynamics. We estimate a battery of Cointegrated Structural Vector Autoregressive models, and we identify structural shocks by employing Independent Component Analysis, a data-driven technique which avoids ad-hoc identification choices. The econometric results suggest that the impact of debt on economic activity is Janus-faced. Public debt shocks have positive and persistent influence on economic activity. In contrast, rising private debt has a milder positive impact on GDP, but it fades out over time. The analysis of the possible transmission mechanisms reveals that public debt crowds-in private consumption and investment. In contrast, mortgage debt fuels consumption and output in the short-run, but shrinks them in the medium-run.
Keywords: E32; E62; C58; H63; 330; Public and Private Debt; Business Cycle Fluctuations; Independent Component Analysis; SVAR Identification